Pair interaction energies and local structures of titanium and nickel atom-pairs in β-Sn type silicon. (June 2018) - Fujima, Nobuhisa; Murakami, Taku; Hoshino, Toshiharu; Fukuhara, Mikio
Abstract: Pair interaction energies (PIEs) of Ti-Ti, Ti-Ni and Ni-Ni pairs and optimized local structures around these pairs in β -Sn type Si are studied by first principles calculation to elucidate typical local structures of transition-metal (TM) atoms in Si-rich amorphous silicides or alloys. In the calculations, TM pairs are located at substitutional sites along a long axis of cuboid Si432 (TM2 Si430 ) supercell (6 × 3 × 6 unit cells of β -Sn type Si) to calculate interatomic distance dependences of PIEs up to 6 Å-distance (up to the 12th nearest neighboring (NN) distance). We find that interatomic distances of Ti-Ti and Ti-Ni pairs with largely negative PIEs agree with those in Si-rich ordered silicides such as TiSi2 and Ti4 Ni4 Si7, and that the optimized local structures around Ti-Ti and Ti-Ni pairs commonly have Si-hexagons, which typically appear in early-TM silicides, and thus expected to be observed in the amorphous Si-rich silicides or alloys. On the contrary, Ni-Ni pair in β -Sn type Si indicates no significant feature in PIE profile or in local structures. Properties of Ni-Ni or Ni-Si bonding in Si-rich silicides may be governed by sp 3 -like Si lattices. Highlights: Interatomic distances of Ti-Ti/Ti-Ni in β-Sn Si with low pair interaction energies agree with those in Ti/Ti-Ni silicide. Optimized local structures around Ti-Ti/Ti-Ni pairs with low pair interaction energies typically show Si-hexagons. Optimized interatomic distances Ni-Ni pair agree with those of (not β-Sn type but) diamond type Si-Si distances.